The third wheel: Diary of a wimpy kid - "Kinney, Jeff" (Penguin: London, 2012)
Share in the hilarious adventures of everyone's favourite wimpy kid, Greg Heffley, in the seventh book in the 'Diary of a Wimpy Kid' series
Keywords: Diary Fiction